Geotechnical maps for recommendation on bored pile capacity in Nakhon Ratchasima municipality, Thailand - Suksun Horpibulsuk (Maejo International Journal of Science and Technology, 2013)
This paper presents the development of geotechnical maps in Nakhon Ratchasima municipality, Nakhon Ratchasima province, Thailand based on the boring logs and in situ test results collected from public and private sector sources. The standard penetration number, N was used to identify the soil type. The soil deposits in Nakhon Ratchasima municipality are divided into three layers: medium-to-stiff silty clay with N < 30, first hard silty clay with 30 < N < 50, and second hard silty clay with N > 50. The medium-to-stiff silty clay layer has a thickness varying from 1.8 to 7.5 metres and an average N value of 14 with a relatively low standard deviation of 1.08. The first hard silty clay layer has a thickness varying from 1.2 to 3.0 metres and an average N value of 42 with a standard deviation of 1.37. For a practical application in foundation engineering in which the pile tips of the bored piles are located in the second hard stratum with N > 50, eight pile tip zones with approximated load capacity are recommended for pile lengths of 3-10 metres.